Efficacy and safety analyses of bevacizumab in neoadjuvant chemotherapy for ovarian cancer: a systematic review and meta-analysis - Wang, Yijun; Wang, Yicong; Wang, Lei; Yuan, He; Yu, Yongai; Liu, Daju (Frontiers in Pharmacology, 2025)
ObjectiveTo assess the efficacy and safety of bevacizumab in neoadjuvant chemotherapy for ovarian cancer through systematic evaluation and meta-analysis.MethodsOnline databases, such as PubMed, Embase, and the Cochrane Library, were searched for relevant articles on the treatment of ovarian cancer patients with interval debulking surgery after neoadjuvant chemotherapy in combination with the bevacizumab regimen using the keywords “Ovarian Neoplasms,” “Bevacizumab,” “Monoclonal antibodies against vascular endothelial growth factor,” “Avastin,” and “Neoadjuvant Therapy.” A meta-analysis of the screened literature, which included randomized controlled trials and cohort studies, was then performed using Stata 15.0 software.ResultsThe meta-analysis included five eligible papers. The test group consisted of 160 patients who received paclitaxel + carboplatin + bevacizumab prior chemotherapy (TCB), whereas the control group consisted 211 patients who received paclitaxel + carboplatin (TC). The results indicate that there was no significant difference between the two groups in terms of the rate of optimal cytoreduction (RR = 1.124, 95% CI: 0.947-1.335, P = 0.182; Heterogeneity: I2 = 40.3%, p = 0.152) and progression-free survival (PFS) (HR = 0.74, 95% CI: 0.48-1.14, p = 0.173; Heterogeneity: I2 = 86%, p = 0.007). Neoadjuvant chemotherapy with bevacizumab did not increase the incidence of adverse events in chemotherapy (RR = 0.88, 95% CI: 0.713-1.088, p = 0.238; Heterogeneity: I2 = 49.5%, p = 0.095). The rate of postoperative complications in the TCB group was comparable to that in the TC group (RR = 0.955, 95% CI:0.672-1.359, p = 0.799; Heterogeneity: I2 = 6.8%, p = 0.368).ConclusionThe use of bevacizumab in neoadjuvant chemotherapy for advanced ovarian cancer was safe and feasible but did not significantly improve the satisfactory tumor reduction rate of interval debulking surgery and had no effect on the prolongation of postoperative PFS. Hence, the use of bevacizumab in preemptive chemotherapy for ovarian cancer should be carefully considered.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-12-0065/, INPLASY2024120065.